2021
DOI: 10.30880/ijie.2021.13.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Groundnut Shell Ash on Laterite Soils Stabilized with Lime for Civil Structures

Abstract: This study considered the practicality of groundnut shell ash (GSA) on laterite stabilized with lime for civil structures. Three site locations of lateritic soil named specimen I, II and III were assembled from Ifewara, Atakunmosa West Local Government Area, Ilesa East Local Government Area, and Ilesa West Local Government, all situated in Osun State, Nigeria. Preliminary tests were wrapped up on the soil specimens in their characteristic states and when stabilized with optimum lime. Compaction, California Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to Mujedu and Adebara [13], it has been observed that groundnut shell ash can be used as a substitute for up to 30% of regular Portland cement in concrete, as stated by Albert et al in 2015 and reiterated by Mujedu and Adebara [13,23]. Furthermore, it has been employed as a supplementary component in conjunction with another additive, as indicated by Adetayo et al [36] in 2021, and Ikumapayi [12]. The replacement of groundnut shell ash (GSA) with ordinary Portland cement (OPC) is expected to enhance the resistance of the resultant concrete against chloride ion penetration.…”
Section: Figure 11 the Mixture Effect On The Cohesionmentioning
confidence: 99%
“…According to Mujedu and Adebara [13], it has been observed that groundnut shell ash can be used as a substitute for up to 30% of regular Portland cement in concrete, as stated by Albert et al in 2015 and reiterated by Mujedu and Adebara [13,23]. Furthermore, it has been employed as a supplementary component in conjunction with another additive, as indicated by Adetayo et al [36] in 2021, and Ikumapayi [12]. The replacement of groundnut shell ash (GSA) with ordinary Portland cement (OPC) is expected to enhance the resistance of the resultant concrete against chloride ion penetration.…”
Section: Figure 11 the Mixture Effect On The Cohesionmentioning
confidence: 99%
“…Assessing the impact of stabilizers on soil strength involves looking at changes in consistency limits, compaction characteristics, undrained cohesion, and modulus of elasticity. The investigation of the durability properties of stabilized soil employed the augmentation of undrained shear strength over many days of curing by increasing the percentage of cement [1][2][3][4][5][6]. The stabilized soil's strength and uniformity increased to a suitable level [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, it's used as a fuel, a filler in animal feed, a substitute for plugs in hard particleboard, and activated carbon. In the semi-arid region, especially during the dry season, the large peanut shell is utilized to feed farmed animals [4]. This study aimed to investigated the effectiveness of groundnuts shell as stabilizer agent.…”
Section: Introductionmentioning
confidence: 99%